From Manipulation to Silence: Examining the Mediating Roles of Workplace Anxiety and Abusive Supervision and Conditioned by Leaders Self-Serving Cognition - Georgia Moschogianni (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: Machiavellianism, which describes leaders pursuing their own interests by followers, has recently attracted the attention of academics. The body of data suggests that leaders’ Machiavellianism has a wide range of negative effects, we examine why and when leaders exhibit Machiavellianism in order to provide guidance on how to avoid it. Methodology: Using a cross-sectional field survey with convenience sampling technique, participants in the study included 211 managers and senior level employees working in service sector SMEs from Athens, Greece’s. The theories were tested using structural equation modeling in a quantitative study. Findings: The findings show that leaders’ Machiavellianism has a significant impact on workplace anxiety and abusive supervision through employee silence. A leader’s self-serving cognition moderates the significant relationship between workplace anxiety, abusive supervision, and employee silence. Based on trait activation theory, current study suggests that when leaders with Machiavellian traits have a weak sense of responsibility for their choices and employee silence, they are more likely to experience workplace anxiety, abusive supervision, and self-serving cognition. Implications/Novel Contribution: The current study offers important theoretical and practical insights for the policy makers for the factors that contribute to leaders’ Machiavellianism and its role towards employee silence. Recommendations and future research directions are suggested.